2016
DOI: 10.14814/phy2.13071
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation increases alveolar hemorrhage in mice infected with influenza A

Abstract: Influenza A virus infection is a common respiratory tract infection. Alveolar hemorrhage has been reported in patients with influenza pneumonia and in mice infected with influenza A. In this study, we investigated the effect of two anticoagulants on alveolar hemorrhage after influenza A virus (IAV) infection of wild‐type mice. Wild‐type mice were anticoagulated with either warfarin or the direct thrombin inhibitor dabigatran etexilate and then infected with a mouse‐adapted influenza virus (A/Puerto Rico/8/34 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 35 publications
(76 reference statements)
1
36
2
Order By: Relevance
“…We found that dabigatran decreased activation of coagulation in the lung measured by TAT levels in the BALF of H1N1 IAV infected mice which was associated with increased pulmonary hemorrhages . However, we could not find any differences in the survival between dabigatran and placebo treated H1N1 IAV infected mice .…”
Section: Introductioncontrasting
confidence: 66%
See 4 more Smart Citations
“…We found that dabigatran decreased activation of coagulation in the lung measured by TAT levels in the BALF of H1N1 IAV infected mice which was associated with increased pulmonary hemorrhages . However, we could not find any differences in the survival between dabigatran and placebo treated H1N1 IAV infected mice .…”
Section: Introductioncontrasting
confidence: 66%
“…We found that dabigatran decreased activation of coagulation in the lung measured by TAT levels in the BALF of H1N1 IAV infected mice which was associated with increased pulmonary hemorrhages . However, we could not find any differences in the survival between dabigatran and placebo treated H1N1 IAV infected mice . Importantly, we observed that anticoagulation with the vitamin‐K antagonist warfarin increased pulmonary hemorrhages and mortality of H1N1 IAV infected mice .…”
Section: Introductioncontrasting
confidence: 54%
See 3 more Smart Citations